PENGARUH EDUKASI GIZI MELALUI VIDEO TIKTOK DAN KOMIK TERHADAP PENINGKATAN PENGETAHUAN ANEMIA PADA REMAJA PUTRI DI SMK NEGERI 41 JAKARTA - Elisa Aprilia Dewi (2022)
Background: Anemia is one of the nutritional problems that is still a global concern these days. According to WHO aged 10-19 years have a risk of suffering from anemia. In Indonesia, the prevalence of anemia has increased to 23,7% in the last five years. One of the ways to prevent anemia in adolescents, especially girl, is through nutrition education. Objective: To determine the effect of nutrition education using Tiktok Video and Comic on improvement of anemia knowledge in adolescent girls in SMK Negeri 41 Jakarta. Method: This research was using quasy experimental with pre-posttest group design on 72 students in class X and XI at SMK Negeri 41 Jakarta which choosed by stratified random sampling. The statictical test used wilcoxon signed rank dan mann whitney. Data collected with online method. Result: There was a difference in responden knowledge before and after being given education using comic (p=0,000) and tiktok video (p=0,000). Conclusion: There is an effect of nutrition education using tiktok video and comic on anemia knowledge in adolescent girls in SMK Negeri 41 Jakarta. Suggestion: Adolescents are expected to implement the information related to anemia and the school is expected to use tiktok video and comic as learning media.